2019
DOI: 10.1016/j.jval.2019.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Choosing Video Instead of In-Clinic Consultations in Primary Care in Israel: Discrete Choice Experiment Among Key Stakeholders—Patients, Primary Care Physicians, and Policy Makers

Abstract: Background: Despite its innovative benefits, the adoption of video consultations (VCs) in primary care settings is complex and slow.Objectives: To quantify the preferences of key stakeholders in Israel's primary care-patients, primary care practitioners, and policy makers-regarding VCs compared with traditional in-clinic consultations (ICC) in nonurgent conditions.Methods: Discrete choice experiment surveys were completed by 508 patients, 311 physicians, and 141 policy makers. These consisted of 12 choice task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 52 publications
2
50
0
Order By: Relevance
“…Similarly, based on a survey of 2,700 patients in the US, Heat (28) stated that 4 in 10 patients began using a new app or digital technology to stay connected to their health care providers at the onset of the COVID-19 epidemic. Previous studies conducted in Israel showed that patients and physicians are willing to use digital technology instead of faceto-face appointments when their preferences are considered (29). Another study found that the high use of HMOs' mobile health apps across the socio-demographic spectrum indicates telemedicine's high perceived usefulness (30).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, based on a survey of 2,700 patients in the US, Heat (28) stated that 4 in 10 patients began using a new app or digital technology to stay connected to their health care providers at the onset of the COVID-19 epidemic. Previous studies conducted in Israel showed that patients and physicians are willing to use digital technology instead of faceto-face appointments when their preferences are considered (29). Another study found that the high use of HMOs' mobile health apps across the socio-demographic spectrum indicates telemedicine's high perceived usefulness (30).…”
Section: Discussionmentioning
confidence: 99%
“…Under optimal conditions, physicians equated the contact through the screen with the contact during an inperson visit, using terms such as 'eye contact' and 'face to face'. These findings were unexpected, given that according to the literature an existing doctorpatient relationship is important both for the video consultation to be successful [14,23] and for patients to be willing to use the service [10,24]. However, visual cues have previously been described as benefits of video consultation, favourably building rapport and communication [14].…”
Section: Findings In Relation To Other Studiesmentioning
confidence: 99%
“…Fourteen of the studies assessed healthcare professional decision making about therapy and disease management [19][20][21][22][23][24][25][26][27][28][29][30][31][32], twelve assessed preferences for organisation characteristics of primary care practices [33][34][35][36][37][38][39][40][41][42][43][44], seven assessed the relative influence of implementation and knowledge translation strategies [45][46][47][48][49][50], and two assessed preferences for information and communication technologies [51,52].…”
Section: Purpose Of Dcementioning
confidence: 99%
“…Ten (29.4%) studies explicitly investigated internal or external validity. Examples of internal or external validity checks used in these studies included using a dominant choice task to assess internal consistency [51], detecting repetitive patterns or strait-lining in response patterns [25], rushing [25], including a duplicate question [26,27,44], tests of transitivity [26,35] using follow-up questions [45], and reviewing consistency of answers [19,35,50]. Studies assessed external validity by comparing the DCE findings with the predicted direction of preferences [19,37] or with findings from previously published surveys or clinical trials [25].…”
Section: Analysis Procedures and Statistical Testsmentioning
confidence: 99%